Random Insertion Reporter Gimmicks Powered by Cut-and-Paste DNA Transposons - Yamato Kasahara; Kentaro Semba; Shinya Watanabe; Kosuke Ishikawa (Biomedicines, 2025)
Transposons are mobile genetic elements capable of moving within the genome. Leveraging this property—particularly the cut-and-paste mechanism of DNA transposons—has enabled the development of technologies for inserting exogenous DNA fragments into host genomes. While targeted integration is a key goal for therapeutic applications, this review highlights the value of their intrinsic randomness. By combining the ability to freely design the DNA cargo with the stochastic nature of transposon integration, it becomes possible to generate highly sensitive reporter cells. These can be used to efficiently identify functional markers, uncover novel signaling pathways, and establish innovative platforms for drug screening. As more subfamilies of transposons become available for research use, their complementary biases may enhance the coverage and diversity of genome-wide screening approaches. Although inherently unpredictable, this strategy embraces randomness as a strength, and we propose that it holds great promise for driving new advances in biology, cellular engineering, and medical research.